The use of binominal logistic regression in performance analysis in handball - Volossovitch, A.; Ferreira, A.P.; Gonçalves, I. (International Journal of Computer Science in Sport, 2002)
Quantitative analysis of performance in Sport Games represents an important component in the coaching process. The use of modern objective and reliable computerized methods provides an exact and detailed record of performance. However not all the obtained information is equally useful and significant for the evaluation of a player`s actions in a competition and their influence on the match result.